1995
DOI: 10.1136/thx.50.12.1234
|View full text |Cite
|
Sign up to set email alerts
|

Epstein-Barr virus replication within pulmonary epithelial cells in cryptogenic fibrosing alveolitis.

Abstract: Background -Cryptogenic fibrosing alveolitis (synonymous with idiopathic pulmonary fibrosis) is a clinically heterogeneous condition in which the precipitating factor is unclear. Both environmental and infective factors have been implicated. An association between Epstein-Barr virus (EBV) and cryptogenic fibrosing alveolitis was suggested over a decade ago by a study based on EBV serology, but the significance of this has been unclear. Methods -Lung tissue obtained surgically from patients (n = 20) with crypto… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

5
111
1
11

Year Published

2000
2000
2017
2017

Publication Types

Select...
4
2
2

Relationship

0
8

Authors

Journals

citations
Cited by 148 publications
(128 citation statements)
references
References 25 publications
5
111
1
11
Order By: Relevance
“…Specifically, Epstein-Barr virus (EBV) DNA and protein have been detected in 40 to 70% of lung tissue of IPF patients, compared with 10 to 17% of lung controls. [2][3][4][5][6][7] Our group has detected viral DNA for EBV, Kaposi's sarcoma-associated herpesvirus (KSHV), and Cytomegalovirus herpesvirus in Ͼ95% of lung samples of IPF patients, with statically higher frequency compared with patients with non-IPF lung diseases. 5 We have developed a model of chronic herpesvirusinduced pulmonary fibrosis infection using the herpesvirus murine gammaherpesvirus 68 (MHV68), a natural pathogen of wild murid rodents that has strong genetic and biological similarities with the human gammaherpesviruses EBV and KSHV.…”
mentioning
confidence: 99%
“…Specifically, Epstein-Barr virus (EBV) DNA and protein have been detected in 40 to 70% of lung tissue of IPF patients, compared with 10 to 17% of lung controls. [2][3][4][5][6][7] Our group has detected viral DNA for EBV, Kaposi's sarcoma-associated herpesvirus (KSHV), and Cytomegalovirus herpesvirus in Ͼ95% of lung samples of IPF patients, with statically higher frequency compared with patients with non-IPF lung diseases. 5 We have developed a model of chronic herpesvirusinduced pulmonary fibrosis infection using the herpesvirus murine gammaherpesvirus 68 (MHV68), a natural pathogen of wild murid rodents that has strong genetic and biological similarities with the human gammaherpesviruses EBV and KSHV.…”
mentioning
confidence: 99%
“…There was no difference in EBV detection when comparing patients with, to those without, immunosuppressive therapy [5]. A later report, including 12 patients with IPF, two with IPF and associated systemic sclerosis, 10 with other pulmonary disorders and three healthy control subjects remained unable to confirm this finding; IHC showed inconsistent focal positive staining with anti-EBV antibodies, but there was neither evidence of EBV-RNA using in situ hybridization nor traces of EBV-DNA following gene amplification [6].…”
Section: Discussionmentioning
confidence: 81%
“…Using monoclonal antibodies against viral antigen, EBV replication within type II alveolar cells was shown to occur in adult cryptogenic fibrosing alveolitis (CFA; idiopathic pulmonary fibrosis, IPF) [5]. As these cells may have a critical role in the deposition of type I collagen in the lung, a direct relationship between viral injury and CFA was suggested [5].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…However, in other group, comprised of interstitial lung disease (ILD) of known cause, the EBV serological profiles were normal [18]. While previous study only proposed the association of EBV to IPF, Egan et al [19] reported replicating EBV within type II alveolar cells of the lower respiratory tract in IPF patients. Furthermore, the authors proposed that EBV may be an immune trigger therefore potentially offering a novel opportunity for treatment of IPF by anti-viral therapy.…”
Section: Epstein-barr Virusmentioning
confidence: 90%